To our men comrades (leaflet)
1928 1928 1920s 2 pages TO OUR MEN COMRADES Comrade! Will you help us to win for your wife the first right of a mother, which is to know that her health and means will allow her to care properly for the children she brings into the world. All fathers know what the strain of child-bearing is to the mother of their children ; how she struggles to do her work faithfully, her strength her courage and her temper often failing. Nearly all women love babies and want to care for them, but they are driven to impatience or carelessness when nerves give way and the work is too heavy to be borne. Surely the mothers, upon whom the burden of the children mainly falls, should be the chief ones to decide when the children shall be born. Wives need a few minutes to rest and a few minutes of pleasure ; they need intervals between the coming of the babies, when the food they eat goes to restore their own strength, and not to feed the child. Only healthy mothers can make really happy homes. We are asking men to treat their wives as comrades, recognising that the work of motherhood is hard and dangerous and that those engaged in it are entitled to rest and protection. Of miners actually mining, 1.1 per thousand die every year of fatal accidents. Of mothers actually engaged in child-bearing, 4 per thousand. Apart from risks, the overdriven mother cannot give her best; any more than can the overdriven worker, whatever his job. Women are more than mothers, they are also human beings. Yesterday they were slaves, but to-day and to-morrow they are your friends and counsellers. They stand beside you to make laws and to build the workers' commonwealth; but they do not forget that the main part of their work is to create its citizens. It is in 292/824/1/118